The effect of synthetic wax additives on adhesive properties of bitumen binders - V. V. Yadykina; O. A. Mikhailova; M. S. Lebedev; E. V. Fomina (Вестник СибАДИ)
Introduction. Currently, in road construction, in order to reduce energy costs and harmful emissions, warm asphalt concrete mixture technologies are being increasingly used. One way to reduce the temperature of asphalt concrete mixture prepared is to use additives based on natural and synthetic waxes. In this regard, it is important to study the influence of wax additives on the properties of bitumen binder as a basic component of asphalt concrete mixture. The adhesion between the binder and the mineral filler is the most important property that determines the durability of an asphalt concrete pavement. The purpose of this article is to study the effect of synthetic wax additives on the adhesive properties of bitumen.Materials and methods. The characteristics of the studied synthetic wax additives Viskodor PV-2, Sasobit and Licomont BS-100 have been presented. To simulate binder aging, the heating method in a thin layer, according to GOST 18180, was used with the temperature control time increased to 9 hours. To assess the adhesion between original and modified bitumen binder, as well as the aged binder, the method of boiling stone material coated with bitumen was used, and the assessment of its appearance in accordance with GOST 11508 was made. The study of the adhesion mechanism for the bitumen binder and the mineral filler was carried out by means of spectral analysis.Results and discussion. The influence of synthetic wax additives on the adhesion between bitumen binder and mineral material was analyzed. A change in the adhesive properties of bitumen modified with the studied additives during thermal-oxidative aging was revealed. A comparison was made of the IR spectra of the original and modified bitumen before and after interaction with stone material and the differences in the mechanisms of affecting the adhesion to the mineral filler by the introduced additives were determined. It has been established that the Viskodor PV-2 additive significantly improves bitumen adhesion. Moreover, the effect of improved bitumen adhesion with this additive remains after thermal-oxidative aging, though slightly reduced. Imported additives Sasobit and Licomont BS-100 have a significantly less impact on the adhesive properties of bitumen.Сonclusion. The results obtained show that the use of synthetic wax additives improves the adhesive properties of bitumen, which can positively affect the durability of the road surface. Since the domestic additive Viskodor PV-2 is superior in the effect of improving the adhesive properties of bitumen compared to the studied additives Sasobit and Licomont BS-100, the introduction of this additive into production instead of expensive imported additives will provide both improvement in the quality of asphalt concrete pavement and reduction of costs.